Thesis works of doctors in Tuva - Maadyr, Maya S. (The New Research of Tuva, 2013)
Article reviews the thesis works of doctors of the Republic of Tuva presented in period from 1968 to 2012.
Keywords: thesis; doctors; medicine; review